Impact of a physician – critical care practitioner pre‐hospital service in Wales on trauma survival: a retrospective analysis of linked registry data. (29th March 2021) - Lyons, J.; Gabbe, B. J.; Rawlinson, D.; Lockey, D.; Fry, R. J.; Akbari, A.; Lyons, R. A.
Summary: The Emergency Medical Retrieval and Transfer Service for Wales launched in 2015. This service delivers senior pre‐hospital doctors and advanced critical care practitioners to the scene of time‐critical life‐ and limb‐threatening incidents to provide advanced decision‐making and pre‐hospital clinical care. The impact of the service on 30‐day mortality was evaluated retrospectively using a data linkage system. The study included patients who sustained moderate‐to‐severe blunt traumatic injuries (injury severity score ≥ 9) between 27 April 2015 and 30 November 2018. The association between pre‐hospital management by the Emergency Medical Retrieval and Transfer Service and 30‐day mortality was assessed using multivariable logistic regression. In total, data from 4035 patients were analysed, of which 412 (10%) were treated by the Emergency Medical Retrieval and Transfer Service. A greater proportion of patients treated by the Emergency Medical Retrieval and Transfer Service had an injury severity score ≥ 16 and Glasgow coma scale ≤ 12 (288 (70%) vs. 1435 (40%) and 126 (31%) vs. 325 (9%), respectively). The unadjusted 30‐day mortality rate was 11.7% for patients managed by the Emergency Medical Retrieval and Transfer Service compared with 9.6% for patients managed by standard pre‐hospital care services. However, after adjustment for differences in case‐mix, the 30‐day mortality rate for patients treated by the Emergency Medical Retrieval and Transfer Service was 37% lower (adjusted odds ratio 0.63 (95%CI 0.41–0.97); p = 0.037). The introduction of an emergency medical retrieval service was associated with a reduction in 30‐day mortality for patients with blunt traumatic injury.